Impact of PhET Simulation-Assisted Problem-Based Learning Model on Students' Problem-Solving Skills - Muhammad Zain Zainulloh Irsyad; Istikaroh Istikaroh; Farisa Chaierunnisa (Universal Education, 2024)
This study aims to examine the effect of Problem-Based Learning (PBL) assisted by PhET simulation on students' problem-solving abilities. Using a quasi-experimental research design with a Nonequivalent Control Group model, this study involved 146 students from four classes, divided into two groups, namely the experimental group that used the PBL model with PhET simulation assistance and the control group that followed the conventional learning method. After a pretest to measure initial problem-solving skills, the experimental group underwent PBL with PhET simulations, while the control group used traditional teaching methods. The results showed that both groups experienced improvement, but the experimental group demonstrated more significant improvement, with higher N-gain values (0.630 compared to 0.407) and larger effect sizes (Cohen's d = 3.52 compared to 2.19). Statistical analysis using the Mann-Whitney U test revealed significant differences in posttest scores, confirming that the PBL model assisted by PhET simulations is more effective in enhancing problem-solving skills compared to conventional learning methods. These findings emphasize the importance of implementing interactive learning approaches in improving students' cognitive abilities, particularly in physics education.